2018
DOI: 10.5194/hess-22-3493-2018
|View full text |Cite
|
Sign up to set email alerts
|

The temporally varying roles of rainfall, snowmelt and soil moisture for debris flow initiation in a snow-dominated system

Abstract: Abstract. Debris flows represent frequent hazards in mountain regions. Though significant effort has been made to predict such events, the trigger conditions as well as the hydrologic disposition of a watershed at the time of debris flow occurrence are not well understood. Traditional intensity-duration threshold techniques to establish trigger conditions generally do not account for distinct influences of rainfall, snowmelt, and antecedent moisture. To improve our knowledge on the connection between debris fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 100 publications
(125 reference statements)
1
44
0
Order By: Relevance
“…With SDS triggered events, soil moisture distributes almost to the same fraction (27%, 29%, 27%) over the three most saturated bins (0%-20%, 20%-40%, 40%-60%). This finding supports earlier studies that showed that convective events can start over both, dry and wet soils (Ford et al, 2015;Mostbauer et al, 2018) and may be important to consider when applying antecedent rainfall models to forecast debris flow initiation (Crozier, 1999;Glade et al, 2000).…”
Section: Identification Of Triggers and Their Temporal And Regional Osupporting
confidence: 91%
See 2 more Smart Citations
“…With SDS triggered events, soil moisture distributes almost to the same fraction (27%, 29%, 27%) over the three most saturated bins (0%-20%, 20%-40%, 40%-60%). This finding supports earlier studies that showed that convective events can start over both, dry and wet soils (Ford et al, 2015;Mostbauer et al, 2018) and may be important to consider when applying antecedent rainfall models to forecast debris flow initiation (Crozier, 1999;Glade et al, 2000).…”
Section: Identification Of Triggers and Their Temporal And Regional Osupporting
confidence: 91%
“…Event days on which at least one torrential flow was observed occurred in 10 out of 12 months (except January, February) across all regions. Reflecting results of Mostbauer et al (2018), intense SM trigger appeared comparatively clustered in May (54 % of all SM event days), followed by June 23%and April (15%). A similar cluster is visible for SDS trigger, which favorably occur in July, representing 48% of all event days of this trigger type.…”
Section: Identification Of Triggers and Their Temporal And Regional Omentioning
confidence: 76%
See 1 more Smart Citation
“…Likewise, an unambiguous sign for considerable influence of SM as debris flow trigger during periods of the year when a snowpack is present are prolonged periods of above-freezing temperatures that can, depending on the temperature and water content of the snowpack, lead to sufficiently intense melt to trigger debris flows or to at least contribute to trigger conditions. This study directly follows up on recent results of Mostbauer et al (2018) who hydrologically modeled an Alpine watershed and identified three relevant sources of water input (high-intensity precipitation, SM, and antecedent soil moisture) that are connected to debris flow occurrence with varying seasonal importance. Here we test for the Montafon region in the Austrian Alps the hypotheses that (1) debris flows in such an environment occur at distinct catchment wetness states and are triggered by water input from different weather conditions, (2) signatures of these distinct triggering processes can be found in larger-scale pattern of the hydrometeorological conditions in the days leading up to a debris flow event, without the need for actual precipitation observations and the associated uncertainties and that (3) the hydrometeorological signatures are robust enough to be used for a probabilistic regional prediction of a region's temporal susceptibility to debris flows occurrence.…”
Section: Introductionmentioning
confidence: 88%
“…Triggering precipitation may origin from long-lasting rainfall (LLR) or short-duration storm (SDS) events that are mostly associated with convective processes (e.g., Berti et al, 1999;Church & Miles, 1987;Mostbauer et al, 2018;Stoffel et al, 2011). In addition, intense snowmelt (SM) can play a considerable role for debris flow initiation in cool regions (Cardinali et al, 2000;Church & Miles, 1987;Mostbauer et al, 2018;Stoffel et al, 2011). Notwithstanding considerable progress over the past years, reliable regional predictions of debris flows remain problematic and need to be improved to reduce human and economic losses (cf.…”
Section: Introductionmentioning
confidence: 99%